Challenging lanthanide relaxation theory: erbium and thulium complexes that show NMR relaxation rates faster than dysprosium and terbium analogues1. Issue 25 (7th July 2015) - Funk, Alexander M.; Harvey, Peter; Finney, Katie-Louise N. A.; Fox, Mark A.; Kenwright, Alan M.; Rogers, Nicola J.; Senanayake, P. Kanthi; Parker, David
<x xml:space="preserve">Abstract</x> The unususal relaxation behaviour of lanthanide complexes in solution exposes the limitations of paramagnetic relaxation theory.